Superhydrophobic Surface for Enhancing the Bioavailability of Salbutamol Sulfate from Cross-Linked Microspheres: Formulation, Characterization, and in vivo Evaluation - Gaber D; Abdoun S; Alfuraihy A; Altasan B; Alsubaiyel A (Dove Medical Press, 2021)
Dalia Gaber,1 Siham Abdoun,1 Ameerah Alfuraihy,2 Bushra Altasan,2 Amal Alsubaiyel1 1Department of Pharmaceutics, College of Pharmacy, Al- Qassim University, Buraidah, Kingdom of Saudi Arabia; 2College of Pharmacy, Al- Qassim University, Buraidah, Kingdom of Saudi ArabiaCorrespondence: Dalia Gaber Email dr_daliaahmed@hotmail.comIntroduction: The aim of the work was to formulate salbutamol sulfate (SB) microspheres by using superhydrophobic surface (SHS) under different processing factors for improving its encapsulation efficiency, controling its release rate, and hence enhancing its bioavailability.Methods: Cross-linked microspheres of chitosan (CN) and carrageenan (KN) were made on a SHS under a glutaraldehyde-saturated atmosphere. The formulations were designed and optimized based on 42 factorial design. Percentage encapsulation efficiency (%EE), particle size, swelling ratio, and in vitro release rate were characterized, and the in vivo performance of optimized formula was investigated in beagle dogs.Results: The results showed that the prepared microspheres have a high %EE (97.11± 0.78%) for F13. The swelling ratio was 4.2 at the end of the 8 hours for the optimized formula, and the in vitro release rate was controlled for 12 hours. In vivo study verified that there was a 1.61-fold enhancement in SB bioavailability from optimized formula (F13) compared to market tablet.Conclusion: The study suggested that microspheres prepared from CN/KN crosslinking on an SHS using glutaraldehyde atmosphere is a promising technique that can encapsulate and sustain the release of water-soluble drugs such as SB in addition to improving its in vivo pharmacokinetic profile.Keywords: cross-linked complex, water-soluble drugs, salbutamol sulfate, sustain release, bioavailability, microspheres, superhydrophobic